Pelatihan Penggunaan Wordwall Sebagai Media Pembelajaran Interaktif dalam Menumbuhkan Literasi Digital di Era Pendidikan Berbasis Teknologi - Titin Kempa; Jems Sopacua; Renny Souhoka (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
Education in the digital era requires elementary schools to develop learning processes that not only focus on cognitive achievement, but also strengthen students' digital literacy from an early age. However, the implementation of technology-based learning in island and remote areas remains limited, particularly in terms of digital media use and students' active participation. This community service program aimed to build elementary school students' digital literacy by applying interactive, game-based learning media through the Wordwall platform at SD Kristen Patti, Maluku Barat Daya Regency. The program employed a participatory and educational approach, involving 17 elementary school students as the primary participants. Activities were conducted through three stages—preparation, implementation, and evaluation—and carried out across three classroom learning sessions. Wordwall served as the primary learning medium, with educational game activities aligned to Indonesian Language, Mathematics, and Natural Science subject matter. The results indicated increased student engagement, learning enthusiasm, and ability to follow digital instructions throughout the learning process. Observational data showed that most students actively participated in learning activities, responded positively to the digital media, and demonstrated greater confidence in classroom interaction. These findings suggest that simple, context-specific digital learning media can be applied effectively even in schools with limited technological resources. The use of Wordwall provided meaningful digital learning experiences and supported the gradual development of students' digital literacy. This program underscores the importance of participatory and sustainable digital learning practices as a strategy to bridge digital literacy gaps in elementary schools located in island and remote areas.